Lumifoil and Tschumi: Virtual projections and architectural interventions. (March 2017) - Bieg, Kory; Odom, Clay
This article introduces the theoretical and technical framework for the design of a temporary rooftop canopy on the red generator—one of the buildings designed by Bernard Tschumi for the Florida International University School of Architecture. The project, Lumifoil, was designed using both top-down and bottom-up computational techniques, including surface modeling via projected geometries and scripted cellular subdivisions and assemblies. Lumifoil attempts to synthesize these two often-conflicting design approaches into a generative design process which leverages context, form, surface, and structure as affective and effective actors. Lumifoil is the result of a design methodology which is both active and reactive to existing conditions of the site and new opportunities afforded by the program. It is contextual in its top-down relationship to Tschumi's existing building and theory, generative in how details emerge bottom-up through scripts which lack any reference to site, and emergent in the resulting synthetic processes and effects which are produced. Through this methodological development, the project both tracks and responds to popular architectural theory and design from the mid-1990s to today. The theoretical underpinnings of the project build upon the idea that the actual (the real-life physical manifestation of matter) and the virtual (the potential for an object to be) are two constantly shifting paradigms in which design processes can intervene to help develop an architectural solution from a range of possibilities. The technical aspect of the project includes the collaborative workflow between the architecture offices of OTA+ and studio MODO with Arup Engineers to resolve structural issues using parametric modeling tools and structural analysis software. The final project is entirely parametric and fabrication is completely automated.